Tekijänoikeuksien monet puolet: Tutkimus tekijänoikeuslukutaidosta kirjastoissa, arkistoissa ja museoissa - Kortelainen, Terttu; Rytinki, Markus (Informaatiotutkimus, 2019)
Copyright literacy in Finnish libraries, archives and museums was studied by a web survey as part of a multinational research. The questionnaire was answered at least partly by 274 and completely by 156 informants who mostly were experienced professionals. The study focused on the awareness of national and international copyright legislation and institutions, regulations concerning different aspects of copyright, and sources of copyright information that the respondents would use. They were moderately well aware of national legislation and copyright institutions, open data and open access, while international regulations were less familiar. The results in many respects corresponds with those of an international survey concerning 13 countries. The most important information sources concerning copyright were the internet, colleagues, books and articles. The informants suggested a great variety of copyright issues for contents of future education, and especially wished for instruction on how to apply legislation in practical cases.